Design improvement and performance analysis of 12slot-10pole permanent magnet flux switching machine with field excitation coils - E, Sulaiman (2011)
Permanent magnet flux switching machine (PMFSM) with additional field excitation coil (FEC) has several attractive features compared to conventional permanent magnet (PM) machines because of its variable flux control capability and robust rotor structure suitable to apply for high speed applications. However, the original machine has a limitation of operating in high current condition due to nonessential magnetic saturation that prevents the machine from extracting the maximum performances. To overcome this problem, some design refinements are conducted by using deterministic optimization method to gain a better performance in the maximum torque and power production. The results simulated by finite element analysis (FEA) show that the machine with the improved design increases by 11.6% of the maximum torque and 16.3% of the maximum power compared to the original design.